THE STUDENTS PERCEPTION OF GOOGLE FORM AS AN ASSESSMENT TOOL IN LISTENING INTEPRETATIVE COURSES - Hajija Souwakil; Wardani Dwi Wihastyanang; Cinta Nayla Sa'diyah; Ayusti Fitri Auliya Rahma (JEELL (Journal of English Education, Linguistics and Literature), 2026)
The transition to online learning during the global pandemic necessitated a rapid shift toward digital evaluation tools within higher education. This study explores students' perceptions of Google Forms as an assessment tool in the Listening Interpretative Course at the English Department of Universitas PGRI Jombang. This study employed a qualitative descriptive methodology. Data were collected through a combination of closed-ended questionnaires and semi-structured interviews with students who utilized Google Forms for their listening assessments. The data were analyzed using the interactive model by Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing. The findings reveal that students generally hold a positive perception of Google Forms, citing its user-friendly interface, accessibility via mobile devices, and the efficiency of instant feedback as primary benefits. However, negative perceptions emerged primarily due to environmental factors, such as unstable internet connectivity and audio synchronization issues, which triggered frustration and temporary rejection of the tool. The study concludes that while Google Forms is an effective instrument for digital evaluation, its success in a listening context depends heavily on stable infrastructure and the maintenance of human-to-human instructional support to mitigate technology-induced anxiety.